Comparative and trend analysis of financial management practices in Southeast Asia Higher Education Institutions (HEIS) / Mohd Rahim Khamis … [et al]. - Khamis, Mohd Rahim; Che Yahya, Norliza; Jaafar, Norlida; Abdullah, Zaini (Research Management Centre (RMC), 2019)
This paper discusses the modernisation effort in financial management (FM) practices and income diversification strategies of higher education institutions (HEIs) in Southeast Asia. This effort and strategies attempt to enhance human, organisational and technical capacities of HEIs in Southeast Asia through systematisation and promotion of good practices. Furthermore, the modernisation effort of FM is also to promote regional integration through the creation of a network amongst financial managers pursuing modernisation in FM systems and practices. The data related to economic and social indicators, are provided by six HEIsin Southeast Asian countries (Indonesia, Thailand and Malaysia). The gathered data were scrutinised to initiate both macro and micro analyses. The six participated HEIs, filled-up a macro and micro observation template. The macro datawas sourced from the World Bank database and Ministry of Higher Education. Meanwhile forthe micro data, information on the financial management of a university wassourced by each participated HEI. The collected information, covering the period from 2013-2015 includes several socio-economic indicators such as GDP per capita, population and unemployment rate of a country and the HEI’s specific information on financial management approach. The data matrix is analysed and presented in graphsto illustrate the average behaviour of the collected data for all the countries and HEI. The results were compiled according to social and economic indicators as well as the HEI’s approach in sourcing for its institution to constitute a diagnosis of financing mechanisms of the HEI.